RORc-expressing immune cells negatively regulate tertiary lymphoid structure formation and support their pro-tumorigenic functions - Cinnamon, Einat; Stein, Ilan; Zino, Elvira; Rabinovich, Stav; Shovman, Yehuda; Schlesinger, Yehuda; Salame, Tomer-Meir; Reich-Zeliger, Shlomit; Albrecht, Thomas; Rössler, Stephanie; Schirmacher, Peter; Lotem, Michal; et al. (Journal of hepatology, 2024)
Background & Aims - RORc-expressing immune cells play important roles in inflammation, autoimmune disease and cancer. They are required for lymphoid organogenesis and have been implicated in tertiary lymphoid structure (TLS) formation. TLSs are formed in many cancer types and have been correlated with better prognosis and response to immunotherapy. In liver cancer, some TLSs are pro-tumorigenic as they harbor tumor progenitor cells and support their growth. The processes involved in TLS development and acquisition of pro- or anti-tumorigenic roles are largely unknown. This study aims to explore the role of RORc-expressing cells in TLS development in the context of inflammation-associated liver cancer. - Methods - IKKβ(EE)Hep mice, exhibiting chronic liver inflammation, TLS formation and liver cancer, were crossed with RORc knockout mice to explore RORc’s effect on TLS and tumor formation. TLS phenotypes were analyzed using transcriptional, proteomic, and immunohistochemical techniques. CD4, CD8, and B-cell depletions were used to assess their contribution to liver TLS and tumor formation. - Results - RORc-expressing cells are detected within TLSs of both human patients and mice developing intrahepatic cholangiocarcinoma. In mice, these cells negatively regulate TLS formation, as excess TLSs form in their absence. CD4 cells are essential for liver TLS formation, while B cells are required for TLS formation specifically in the absence of RORc-expressing cells. Importantly, in chronically inflamed livers lacking RORc-expressing cells, TLSs become anti-tumorigenic, reducing tumor load. Anti-tumorigenic TLSs revealed enrichment of exhausted CD8 cells with effector functions, germinal center B cells and plasma cells. B cells are key in limiting tumor development, possibly via tumor-directed antibodies. - Conclusions - RORc-expressing cells negatively regulate B-cell responses and facilitate the pro-tumorigenic functions of hepatic TLSs. - Impact and implications - RORc-expressing immune cells play critical roles in immune regulation, yet their specific influence on tertiary lymphoid structures (TLSs) in liver pathology and cancer has not been elucidated. Our study reveals that RORc-expressing cells act as negative regulators of TLS formation and shape the immune microenvironment in a manner that promotes tumor development. In the absence of RORc-expressing cells, TLSs not only increase in number but also acquire anti-tumorigenic properties. These findings suggest that RORc-expressing cells serve as key modulators of liver immune dynamics, with potential implications for the use of RORc as a biomarker to differentiate between pro- and anti-tumorigenic immune environments and as a target for manipulating TLS abundance and phenotype in liver cancer.